Hubungan Keragaman Makanan dan Perkembangan Balita Stunting di Kecamatan Cisayong Kabupaten Tasikmalaya Indonesia: The Relationship between Food Diversity and Development of Stunted Toddlers in Cisayong District, Tasikmalaya Regency, Indonesia - Lina, Nur; Novianti, Siti; Gustaman, Rian Arie; Rohmania, Diah (Amerta Nutrition, 2024)
Background: Stunting is chronic malnutrition causes impaired physical growth, cognitive functions, motor skills, decreased physical capacity, and nerve development. The prevalence of stunting in Tasikmalaya Regency was 24.4% in 2021 then increased to 27.2% in 2022. One of the stunting locus villages in Tasikmalaya Regency is Cisayong. Objectives: The primary aim of the study was to analyze the relationship between food diversity and the development of stunted toddlers in Cisayong Village, Tasikmalaya Regency. Methods: Case control study with a population of toddlers aged 24-59 months based on toddler weighing data in February 2023. The samples were calculated based on the Lemeshow formula involving 49 toddlers in the case group and 98 toddlers in the control group. The adopted research instruments were the food diversity score questionnaire and the Pre-Development Screening Questionnaire (KPSP). Results: Most toddlers (57.14%) consumed a variety of foods, (62.59%) indicated developmental stages that did not match the KPSP. The results of the Mann Whitney test produced a p-value of 0.47 indicating that there was no significant difference in the variety of food consumed by toddlers. Toddlers whose developmental stages did not match were more often identified in stunted toddlers rather than well-grown toddlers. In particular, there was a significant difference in developmental level scores between the two groups of toddlers (p-value<0.001). Conclusions: Well-grown toddlers indicated the same differences in terms of food diversity. There was a difference in developmental level scores between the two groups of toddlers.